MEASUREMENT AND MULTIFACTORIAL ANALYSIS OF STUDENTS’ PATRIOTISM - Maslak, Anatoly; Pozdnyakov, Stanislav (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
The relevance of the work is based on internal and external causes. Internal reasons consist of the fundamental transformation and revaluation of values occurring in Russia. Patriotism is the foundation of responsibility for the preservation of spiritual values and the power of the country. External causes are the need to counter terrorism and conflicts in the world. The goal of the study is to measure the level of patriotism of students according to their gender, course, and department of the branch of Kuban State University in Slavyansk-on-Kuban. To accomplish this goal, it is necessary to assess the quality of the questionnaire as a measuring tool and measure the level of patriotism of students on a linear scale. The theory of latent variables is used as the method of research, allowing to measure the level of patriotism on a linear scale.